Activation of the innate immunity in Drosophila by endogenous chromosomal DNA that escaped apoptotic degradation - Mukae, Naomi (Cold Spring Harbor Laboratory Press, 2002)
Apoptotic cell death is accompanied by degradation of chromosomal DNA. Here, we established in Drosophila a null mutation in the gene for inhibitor of caspase-activated DNase (ICAD) by P-element insertion. We also identified a loss-of-function mutant in Drosophila for DNase II-like acid DNase. The flies deficient in the ICAD gene did not express CAD, and did not undergo apoptotic DNA fragmentation during embryogenesis and oogenesis. In contrast, the deficiency of DNase II enhanced the apoptotic DNA fragmentation in the embryos and ovary, but paradoxically, the mutant flies accumulated a large amount of DNA, particularly in the ovary. This accumulation of DNA in the DNase II mutants caused the constitutive expression of the antibacterial genes for diptericin and attacin, which are usually activated during bacterial infection. The expression of these genes was further enhanced in flies lacking both dICAD and DNase II. These results indicated that CAD and DNase II work independently to degrade chromosomal DNA during apoptosis, and if the DNA is left undigested, it can activate the innate immunity in Drosophila.